Investigation of NavIC and GPS Multipath Phase for Soil Moisture Studies - Shekhar, Sushant; Prakash, Rishi; Vidyarthi, Anurag (Journal of Graphic Era University, 2021)
This paper aims to investigate the relationship between the multipath phase of Global Navigation Satellite System (GNSS) and volumetric moisture content (VMC) of soil. The carrier to noise ratio (C/No) data of multipath signals at two different frequencies has been analyzed. The first one is India’s NavIC L5 frequency (∼1176 MHz) and the second one is GPS L1 frequency (∼1575 MHz). The received multipath signals are highly dependent on dielectric value of soil and the elevation angle of satellite. The relationship drawn for the NavIC and GPS C/No data is based on multipath phase analysis and in situ soil moisture. The values of correlation coefficient observed between these parameters were 0.9 and 0.63 for NavIC and GPS multipath signal respectively. The result from both GNSS shows good sensitivity and could be used to estimate the soil moisture for agricultural land